3D stimulated Raman spectral imaging of water dynamics associated with pectin-glycocalyceal entanglement - Floess, Moritz; Steinle, Tobias; Werner, Florian; Wang, Yunshan; Wagner, Willi Linus; Wagner, Verena; Liu, Betty; Zheng, Yifan; Chen, Zi; Ackermann, Maximilian; Mentzer, Steven J.; Giessen, Harald (Biomedical optics express, 2023)
Pectin is a heteropolysaccharide responsible for the structural integrity of the cell walls of terrestrial plants. When applied to the surface of mammalian visceral organs, pectin films form a strong physical bond with the surface glycocalyx. A potential mechanism of pectin adhesion to the glycocalyx is the water-dependent entanglement of pectin polysaccharide chains with the glycocalyx. A better understanding of such fundamental mechanisms regarding the water transport dynamics in pectin hydrogels is of importance for medical applications, e.g., surgical wound sealing. We report on the water transport dynamics in hydrating glass-phase pectin films with particular emphasis on the water content at the pectin-glycocalyceal interface. We used label-free 3D stimulated Raman scattering (SRS) spectral imaging to provide insights into the pectin-tissue adhesive interface without the confounding effects of sample fixation, dehydration, shrinkage, or staining.
Gesehen am 15.11.2023